My Library At Sutera Mall: A Library With A Unique Backdrop (Consal XVI Conference In Bangkok, June 2015) - Aljunied, Zahra (2015)
This paper intends to present to the conference a unique model of a community/public library set up in the state of Johor in Malaysia. My Library in the Sutera Mall Shopping Centre is a corporate social responsibility project of the Tanah Sutera Development Sendirian Berhad (the owner of the Sutera Mall, a private limited company based in Malaysia and deal in properties). As part of its expansionplan, the Sutera Mall management has taken a big step in embarking on a project to set up a library within the shopping mall. This is indeed a noble undertaking by the mall management to play their part in the efforts to promote reading and knowledge acquisition among the communities. The paper will highlight the process of the library development from the conceptualization of the idea to the preparation for the physical and other set up of the library which covers a compressed timeline made possible only through innovative system and creative ways of doing things differently from the given norms in a typical library development project. .